The Hegemonic Masculinity Depiction in Steven Knight’s Peaky Blinders TV Series - Diana Nurlaila (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2022)
Peaky Blinders is a gangster TV series which depict a highly patriarchal society in the 1920s Birmingham. The depiction of the main male character is closely related to hegemonic masculinity traits, such as aggressive, stoic, and autocratic leadership style. Connell suggests that to maintain male power, female subordination is necessary (Connell, 2003). This study aims to reveal how hegemonic masculinity is promoted in Peaky Blinders from a gender perspective initiated by Connell. Furthermore, this study also examines the gender relation between each gender configuration which appears in this series. The discussion is divided into two main sections. First, the researcher demonstrates how the main male characters in this series practice hegemonic masculinity. Second, the researcher demonstrates how the role of each gender configuration in the Peaky Blinders series contributes to the construction of hegemonic masculinity. The result of the reading show how Thomas Shelby as main character exhibits traits associated with hegemonic masculinity such as being rude and aggressive, supporting male dominance over women, employing authoritarian leadership styles, and suppressing various types of emotions associated with weakness. Keywords: hegemonic masculinity, aggressiveness, stoicism, autocratic, gender, gender hierarchy